Comparative effectiveness and safety of extended anticoagulant therapy among Medicare beneficiaries with venous thromboembolism - Haesuk Park; Hye‐Rim Kang; Pei‐Lin Huang; Wei‐Hsuan Lo‐Ciganic; Christina E. DeRemer; Debbie Wilson; Eric A. Dietrich (Wiley, 2023)
Abstract Guidelines recommend an extended course of anticoagulation therapy for patients who experienced venous thromboembolism (VTE) without transient provocation, however, optimal duration remains uncertain. We assessed effectiveness and safety of extended use of apixaban and warfarin greater than 6 months of initial treatment in patients with VTE. We conducted a retrospective cohort study of Medicare beneficiaries aged greater than or equal to 18 years with deep vein thrombosis or pulmonary embolism. Patients were required to have initiated anticoagulants within 30 days of their first VTE diagnosis, completed 6 months of initial anticoagulant treatment, and received extended phase treatment with apixaban (the apixaban group) or warfarin (the warfarin group) or no extended therapy. Multivariable Cox proportional hazards modeling with inverse probability treatment weighting was used to compare recurrent VTE, mortality, and major bleeding risks among the three groups. Mean extended‐treatment duration was up to 10 months and 14 months in apixaban and warfarin groups, respectively. Compared with no extended treatment, apixaban use was associated with decreased risks of recurrent VTE (hazard ratio [HR] = 0.08, [95% confidence interval [CI]: 0.01-0.41]) and mortality (HR = 0.37, [95% CI: 0.27-0.51]) without increased major bleeding risk (HR = 1.29, [95% CI: 0.68-2.45]); warfarin use was associated not with recurrent VTE risk change but with increased major bleeding risk (HR = 2.14, [95% CI: 1.26-3.65]) and decreased mortality risk (HR = 0.39, [95% CI: 0.29-0.51]). Compared with warfarin, apixaban use was associated with decreased recurrent VTE (HR = 0.13, [95% CI: 0.03-0.63]) and major bleeding (HR = 0.56, [95% CI: 0.32-0.98]) risks. Subgroup and sensitivity analyses (e.g., intention‐to‐treat) findings remained consistent. Compared with warfarin or no extended therapy, extended‐apixaban use was associated with reduced risk of recurrent VTE without increased major bleeding risk. Continuing anticoagulant therapy with apixaban greater than 6 months may be effective and safe.